Validasi Metode Analisis Ofloksasin dalam Plasma In Vitro secara Kromatografi Cair Kinerja Tinggi-Fluoresensi Mengacu pada European Medicines Agency Guideline - Tania, Letitia; Sitepu, Eme Stepani; Harahap, Yahdiana (UI Scholars Hub, 2016)
Ofloxacin is an antibiotic from second generation of fluoroquinolones group. Concentration of ofloxacin in human plasma is in low level, and due to that fact, it requires a selective, accurate, sensitive method of analysis. In this study, the optimization and validation of ofloxacin analysis in human plasma using high performance liquid chromatography-fluorescence with ciprofloxacin-HCl as an internal standard were carried out. Separation of ofloxacin was performed using C18 (Waters, SunfireTM 5 µm; 250 x 4.6 mm) column with an isocratic mobile phase consisted of triethylamine 1% in water pH 3.0–acetonitrile (84:16) in the flow rate of 1.0 mL/min, 40oC column temperature whereas the detection was carried out at excitation of 300 nm and emission of 500 nm. Plasma extraction was done by deproteination using methanol, through the process of vortex and centrifugation (10000 rpm) for 2 minutes and 10 minutes consecutively. The method was valid and linear within the concentration ranged from 21,4 ng/mL to 4280 ng/mL with LLOQ of 21,4 ng/mL. Intra-day and inter-day accuracy and presicion was not more than + 20% for LLOQ and not more than + 15% for QCL, QCM, and QCH samples in both % diff and coefficient of variation. Ofloxacin was stable in human plasma at least three freeze and thaw cycle, for at least 24 hours in room temperature and 28 days at -20oC. This bioanalytical method fulfilled the acceptance criteria following EMEA guideline.